Monitoring protein-metal binding by 19F NMR – a case study with the New Delhi metallo-β-lactamase 1 - Mrs ZAHN GOWAR; Rydzik, AM; Brem, J; Chandler, SA; Benesch, JLP; Claridge, TDW; Schofield, CJ (Royal Society of Chemistry, 2020)
19F NMR protein observed spectroscopy is evaluated as a method for analysing protein metal binding using the New Delhi metallo-β-lactamase 1. The results imply 19F NMR is useful for analysis of different metallated protein states and investigations on equilibrium states in the presence of inhibitors. One limitation is that 19F labelling may affect metal ion binding. The sensitive readout of changes in protein behaviour observed by 19F NMR spectra coupled with the broad scope of tolerated conditions (e.g. buffer variations) means 19F NMR should be further investigated for studying metal ion interactions and the inhibition of metallo-enzymes during drug discovery.